A Policy Review of the Tourism Ecosystem Paradigm in Indonesia's Law No. 18/2025 - Bintari Pangesti Putri; Mega Fitriani Adiwarna Prawira; Rumba (Journal of Tourism Sustainability, 2026)
Indonesia's Law No. 18/2025 marks a decisive shift from a quantity-driven framework to a quality-focused "Tourism Ecosystem." However, the governance consequences of this deregulation remain under-theorized. Employing a critical socio-legal approach and systems theory, this article contrasts the 2025 reform with Law No. 10 of 2009. The study identifies a "Regulatory Grand Bargain" producing a "Tight-Loose Governance Paradox." Specifically, the state trades structural decentralisation—achieved by abolishing the single-bar industry association—for functional intensification through mandatory Competency Certification and strict carrying-capacity limits. While this architecture advances sustainable tourism, it exposes vulnerabilities: an "orchestration deficit" in intersectoral coordination and the risk of social exclusion for community-based actors. To mitigate these unintended outcomes, the study recommends establishing a digital orchestration platform to enhance policy coherence and implementing affirmative certification subsidies to ensure equitable participation across the new tourism ecosystem.